Periodic respiration in erect posture in Shy-Drager syndrome. Issue 11 (November 1978) - Chokroverty, S; Sharp, J T; Barron, K D
Abstract : Tilt-table polygraphic study in four patients with Shy-Drager syndrome demonstrated periodic apnoea in the erect posture. In one patient reduced hypercapneic ventilatory response and necropsy findings of neuronal loss and astrocytosis in the pontine tegmentum suggested dysfunctional respiratory neurones in the brainstem. One patient had Cheyne-Stokes respiration during the late stage of the illness.